Application of plant hydrosols for decontamination of wheat, lentil and mung bean seeds prior to sprouting - Sahan, N.; Tornuk, F. (CODON PUBLICATIONS, 2016)
It is a requirement for both minimally processed and ready-to-eat fruit and vegetable industry and consumers to decrease use of harmful chemical antimicrobial agents such as chlorinated compounds in fresh product sanitation since they have a number of negative health and environmental effects. In this study, washing treatments with summer savoury, bayleaf and thyme hydrosols that are by-products essential oils were assessed for decontamination of wheat, mung bean and lentil seeds contaminated with Salmonella Typhimurium and Staphylococcus aureus prior to sprout production. Initial levels of S. aureus on wheat, lentil and mung bean were 4.86, 4.24 and 4.23 log colony forming units/g, respectively. Hydrosol treatments reduced S. aureus numbers significantly (P summer savoury>bayleaf. Therefore, this study confirmed that plant hydrosols, especially thyme had potential to be used as a natural disinfectant for sanitation of seeds prior to germination in order to ensure their microbiological safety.
Keywords: seed sprout; germination; hydrosol; decontamination; thyme; ESCHERICHIA-COLI O157-H7; AQUEOUS CHLORINE DIOXIDE; INOCULATED ALFALFA SEEDS; STAPHYLOCOCCUS-AUREUS; UNITED-STATES; SALMONELLA; OUTBREAK; EFFICACY; DISINFECTION; IRRADIATION; Food Science & Technology